2003
DOI: 10.1038/nn1106
|View full text |Cite
|
Sign up to set email alerts
|

Adenylyl cyclase I regulates AMPA receptor trafficking during mouse cortical 'barrel' map development

Abstract: Cortical map formation requires the accurate targeting, synaptogenesis, elaboration and refinement of thalamocortical afferents. Here we demonstrate the role of Ca2+/calmodulin-activated type-I adenylyl cyclase (AC1) in regulating the strength of thalamocortical synapses through modulation of AMPA receptor (AMPAR) trafficking using barrelless mice, a mutant without AC1 activity or cortical 'barrel' maps. Barrelless synapses are stuck in an immature state that contains few functional AMPARs that are rarely sile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
119
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(138 citation statements)
references
References 50 publications
18
119
1
Order By: Relevance
“…Developmentally, dysregulation of the cAMP cascade is known to impact growth cone motility and the structure of terminal varicosities in Drosophila (Kim and Wu 1996). Cyclic AMP plays an important role in AMPA trafficking (Lu, She et al 2003), cell survival and neurogenesis (Nakagawa, Kim et al 2002), neural induction (Otte, van Run et al 1989), neurite formation, and synaptogenesis (Takuro Tojima 2003). Cyclic AMP also regulates spine density by gating brain derived neurotrophic factor (BDNF) signaling, a neurotrophin implicated in dendrite formation (Ji, Pang et al 2005).…”
Section: Cyclic Amp Theory Of Fragile Xmentioning
confidence: 99%
“…Developmentally, dysregulation of the cAMP cascade is known to impact growth cone motility and the structure of terminal varicosities in Drosophila (Kim and Wu 1996). Cyclic AMP plays an important role in AMPA trafficking (Lu, She et al 2003), cell survival and neurogenesis (Nakagawa, Kim et al 2002), neural induction (Otte, van Run et al 1989), neurite formation, and synaptogenesis (Takuro Tojima 2003). Cyclic AMP also regulates spine density by gating brain derived neurotrophic factor (BDNF) signaling, a neurotrophin implicated in dendrite formation (Ji, Pang et al 2005).…”
Section: Cyclic Amp Theory Of Fragile Xmentioning
confidence: 99%
“…NMDA receptor blockade (Crair and Malenka, 2005), and PKA RIIβ deletion both prevent thalamocortical LTP during early development (Watson et al, 2006) but cortical deletion of the critical NMDA receptor subunit NR1 (Iwasato et al, 2000) and deletion of PKA RIIβ (Watson et al, 2006;Inan et al, 2006), while blurring barrel boundaries, do not completely disrupt formation of somatosensory cortical barrels. Finally, while studies have suggested the importance of GluR1 trafficking for thalamocortical long-term potentiation (Lu et al, 2003), barrels form normally in GluR1 KO mice (Watson et al, 2006), again suggesting that thalamocortical LTP may not be essential for the development of somatosensory cortical barrels. This would suggest that the lack of thalamocortical LTP is unlikely to be the sole direct cause of the lack of development of somatosensory cortical barrels in Emx1-cre;Dnmt1 mutants.…”
Section: Discussionmentioning
confidence: 97%
“…Considerable controversy exists on whether thalamocortical long-term potentiation is essential for barrel formation. Barrel formation and thalamocortical plasticity are both disrupted by adenylyl cyclase I deletion (Abdel Majid et al, 1998;Lu et al, 2003). NMDA receptor blockade (Crair and Malenka, 2005), and PKA RIIβ deletion both prevent thalamocortical LTP during early development (Watson et al, 2006) but cortical deletion of the critical NMDA receptor subunit NR1 (Iwasato et al, 2000) and deletion of PKA RIIβ (Watson et al, 2006;Inan et al, 2006), while blurring barrel boundaries, do not completely disrupt formation of somatosensory cortical barrels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations